Potential association between M694V homozygous mutation in familial Mediterranean fever and eosinophilic intestinal inflammation: a pediatric case series - G. Dingulu; G. Dingulu; G. Dingulu; D. Berrebi; C. Martinez-Vinson; C. Dumaine; C. Dumaine; I. Melki; I. Melki; I. Melki; J. Viala; Z. Valtuile; et al. (Frontiers Media S.A., 2024)
Familial Mediterranean fever (FMF) is the most common hereditary systemic auto-inflammatory disease. Digestive complaint is a common feature during FMF attacks. Nevertheless, digestive complaint in attack-free period has scarcely been studied. This retrospective monocentric study aimed to describe the clinical, histological, and genetic features of pediatric patients with FMF who underwent endo-colonoscopy in this setting. Out of 115 patients with a diagnosis of FMF, 10 (8, 7%) underwent endoscopy or colonoscopy. All displayed homozygote MEFV M694V mutation and presented chronic abdominal pain, iron deficiency, and/or growth retardation. On the histological level, all patients displayed low-grade mucosal inflammation, characterized by a moderate eosinophilic infiltrate in the lamina propria sometimes associated with increased crypt apoptosis. The proportion of patients explored with endoscopy or colonoscopy was 0.4 patients per year in our center, compared with 5.7 patients per year nationwide. This study identified a specific intestinal phenotype that does not respond to the criteria of classical inflammatory bowel disease: pediatric FMF pediatric patients with homozygous MEFV M694V, abdominal pain, iron deficiency, and growth retardation should benefit from specialized gastroenterological advice.